MODEL PROFESSIONAL DEVELOPMENT BERBASIS INTERNET UNTUK MENINGKATKAN TEAM LEARNING SEKOLAH - Farida Wulandari; Hendarman Hendarman (JURNAL MANAJEMEN PENDIDIKAN, 2021)
INTERNET BASED PROFESSIONAL DEVELOPMENT MODEL TO IMPROVE SCHOOL LEARNING TEAMThe tendency of the fact where the teachers do not need to learn or do not want to improve professional competence is a reflection of the opposite of team learning. Schools need to improve their performance to achieve maximum results. This study aimed to analyze an Internet-Based Professional Development model that can improve the ability of kindergarten teachers to carry out professional development independently and build team learning as well. Internet-Based Professional Development is an alternative effort in overcoming the improvement of kindergarten teachers' ability to organize Professional Development as well as team-learning. Limited trial research was conducted at Smartskul Preschool Kindergarten with 5 teachers. Extensive trials were carried out at TKI Al-Hamidiyah Depok with 25 teachers, and at TKIT Aliya Bogor with 13 teachers. The method of research used was research and model development (Research Professional Development / R D). Each trial carried out three times actions in limited trials and two actions in extensive trials at each school. In this study, the data analysis used was qualitative, quantitative, and formative. To measure the validity, this research used non-test and expert judgment. The Internet-Based Professional Development model consisted of input, process, and output. The input consisted of the Internet-Based Professional Development module, and kindergarten teachers and principals. The process consisted of planning, implementing monitoring, as well as evaluation reflection. The output of the Internet-Based Professional Development model was able to improve the ability of kindergarten teachers in organizing Internet-Based Professional Development as well as being able to build team learning.